2021
DOI: 10.1002/jsfa.11328
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation for phytochemical composition and regulation of blood glucose, hepatic oxidative stress and insulin resistance in mice and HepG2 models of four typical Chinese dark teas

Abstract: BACKGROUND: Dark tea, comprising one of the six major teas, has many biological activities, which originate from their active substrates, such as polyphenols, polysaccharides, and so on. The hypoglycemic effect is one of its most prominent activities, although less is known about their evaluation and potential role in the hypoglycemic mechanism.RESULTS: In the present study, we separately analyzed the phytochemical composition, glycosidase inhibition and free radical scavenging activities, and hypoglycemic act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 53 publications
(54 reference statements)
0
21
0
Order By: Relevance
“…Chlorophyll catabolites are an indispensable part of phytochemicals and human nutrition, as Karg et al (2021) reported that a phylloxanthobilin (a yellow chlorophyll catabolite) possesses antioxidative and anti-inflammatory activities. Citrobacter and unclassified Enterobacteriaceae abundances were also positively correlated with fructose and mannose metabolism, which may be related to the reduction of hyperglycemia by drinking FBT ( p < 0.05) ( Zhu et al, 2021 ); Comamonas abundances were also closely associated with the functions of homologous recombination, pyrimidine metabolism, and quorum sensing. In contrast, Enterobacter abundances were more associated with the metabolism pathways of glycerophospholipid metabolism ( Figure 4C ), which may participate in inhibiting fat accumulation and avoiding fatty liver produced ( Wu et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Chlorophyll catabolites are an indispensable part of phytochemicals and human nutrition, as Karg et al (2021) reported that a phylloxanthobilin (a yellow chlorophyll catabolite) possesses antioxidative and anti-inflammatory activities. Citrobacter and unclassified Enterobacteriaceae abundances were also positively correlated with fructose and mannose metabolism, which may be related to the reduction of hyperglycemia by drinking FBT ( p < 0.05) ( Zhu et al, 2021 ); Comamonas abundances were also closely associated with the functions of homologous recombination, pyrimidine metabolism, and quorum sensing. In contrast, Enterobacter abundances were more associated with the metabolism pathways of glycerophospholipid metabolism ( Figure 4C ), which may participate in inhibiting fat accumulation and avoiding fatty liver produced ( Wu et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Also, all cells have defense functions to resist peroxidative damage and protect cells from ROS damage, these members include SOD, CAT, GSH-Px (Shen et al, 2016). SOD can catalyze the disproportionation of superoxide anion into oxygen and hydrogen peroxide, CAT can decompose hydrogen peroxide into water and oxygen, and GSH-Px can convert toxic peroxide into non-toxic peroxide by redox glutathione (Zhu et al, 2021a). In this study, the activities of related antioxidant enzymes including SOD, CAT, and GSH-Px in H 2 O 2 -induced HDF-1 cells or galactose-evoked aging mice were significantly decreased, and the MDA level was greatly increased.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress has been reported to be associated with many diseases, such as cancer, Alzheimer’s disease, nephritis, arteriosclerosis, and diabetes, due to the overproduction of oxygen free radicals [ 4 ]. The liver is a vital detoxification organ in the human body and plays a key role in the metabolism of various endogenous and exogenous harmful substances [ 3 ].…”
Section: In Vivo Bioactivity Of Tpsmentioning
confidence: 99%
“…Tea not only creates a lot of wealth but also generates tea culture and tea ceremony [ 1 ]. As a result, tea has become one of the most popular beverages in the world after water [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation